Factors affecting Safety Performance in Repair, Maintenance, Alteration, and Addition (RMAA) Projects - Enshassi, Adnan; Risqa, Ehsan; Arain, Faisal (International Journal of Sustainable Construction Engineering and Technology, 2014)
Repair, Maintenance, Alteration and Addition (RMAA) works are playing an increasingly important role in developing countries. The accidents and fatalities records of RMAA sector in Gaza Strip have been alarmingly high; however, research in the RMAA sector remains limited. Safety of RMAA works has long been neglected because the project sizes of RMAA are small and only last for a short period of time, which make the working environment of RMAA works more difficult to control than new building works. The aim of this paper is to identify, valuate and rank the most important factors that affect safety performance and the most important causes of fatal accidents in RMAA projects. A questionnaire survey was used in this study. The results revealed that poor safety awareness of managers in maintenance firms and lack of training of RMAA workers for handling multi-tasks were the most important factors that affecting safety performance of RMAA works. The results showed that ineffectiveness of lack of training and certification of competence; immature corporate systems of firms which does not care with safety and health through RMAA works, and lack of leadership from government as a key client are the most significant causes of construction fatal accidents of RMAA projects. The results also indicated that the macro level factor is the most important category that causes fatal accidents in RMAA works. It is recommended to enhance the awareness of construction firms, project managers and workers regarding the importance of safety performance in repair and maintenance works and strengthen site monitoring and supervision system in construction firms. Safety training courses should be organized for workers and project managers in order to improve their safety culture and competence regarding safety performance through repair and maintenance works. Furthermore the RMAA subcontractors should be selected according to their good records of safety performance.